Positioning Adat Law in the Indonesia’s Legal System: Historical Discourse and Current Development on Customary Law - Budi Priambodo, Bono (Udayana Journal of Law and Culture; Vol 2 No 2 (2018): Encouraging Cultural Approach to LawDO - 10.24843/UJLC.2018.v02.i02.p02, 2018)
Adat law has been narrowly understood, mainly as part of private law, in the curricula of Indonesian law schools. This is in contrary to the original intent of adat law, both as an academic and policy discourse, at the first place, which was as an attempt to develop a legal system that is suitable to govern the Netherlands East Indies (NEI) for preventing violation against the indigenous sense of justice. This article seeks to clarify the actual purpose of Adat Law, as it conceived, in the living of traditional community and the relation between adat law and Indonesian state law following the Indonesian independence. Subsequently, this article would explore how constitutional law and administrative laws ( staatsrecht ) would place “Adat law” under the Indonesian legal system that might be well claimed as an autochthonous law of Indonesia. It is a legal writing that uses historical, statutory, and case approaches. It has been found out that Adat Law scholarship had a pragmatic purpose i.e. to administer justice and govern the NEI colony that reflects a characteristic of public law. The later development showed that the law has shifted its focus into private law fields such as the law of persons, marriage and family laws, property and inheritance laws. Such shifting leads Adat law into an obscured relation between Adat Law and public laws in the era of the post-independence of Indonesia. It can be concluded that under historical inquiry, the Basic Law of 1945 (Indonesian Constitution) has strongly inspired by Adat Law. The same goes for administrative law, which in this case is represented by BAL that governs not only land administration but all kinds of natural resources in Indonesia until nowadays.